Nosferatu [videorecording (DVD)] - Eggers, Robert, 1983-; Skarsgård, Bill; Hoult, Nicholas, 1989-; Depp, Lily-Rose, 1999-; Taylor-Johnson, Aaron, 1990-; Corrin, Emma, 1995-; Ineson, Ralph, 1969-; McBurney, Simon; Dafoe, Willem; Blaschke, Jarin, 1978-; Carolan, Robin; Stoker, Bram, 1847-1912 (Focus Features, 2025)
A gothic tale of obsession between a haunted young woman and the terrifying vampire infatuated with her, causing untold horror in its wake.